The Structure Modeling of Material Composed of the Orthotropic Crystals - Dabulytė, J.; Ivanauskas, F.; Skakauskas, V.; Barauskas, R. (Nonlinear Analysis: Modelling and Control, 2004)
In this paper the model of a elastic composite medium which consists of a matrix containing a set of orthotropic crystals with the random orientation of the anisotropy axes is presented. The axes orientation is described by the Gauss distribution. The numerical investigation is proposed for rectangular plate, when the normal strains are given in the one side. Other sides are free of strain. The finite - difference technique is used for model discretization.